Kesenjangan Ekonomi Digital di Indonesia: Penyusunan Indeks Ekonomi Digital dan Klasifikasi Provinsi Tahun 2024 - Risky, Risky; Natalia, Desa Ayu (Seminar Nasional Official Statistics, 2025)
The digital economy plays a vital role in supporting inclusive and sustainable economic growth. However, accurately measuring the state of the digital economy in Indonesia remains a challenge. This study aims to develop a Digital Economy Index (IED) for 2024 that reflects the level of readiness of supporting infrastructure for the digital economy and the classification of IED at the provincial level. The index is based on data from the 2024 National Socio-Economic Survey (Susenas) and the Village Potential Survey (Podes), utilizing nine indicators grouped into three main dimensions: digital and economic infrastructure, internet accessibility, and access to economic facilities. Factor analysis was used to reduce indicators and assign weights, followed by linear aggregation to form a composite index. The Jenks Natural Breaks classification method was used to categorize provinces into low, medium, and high groups. The findings reveal significant digital disparities across regions. Provinces in Java and parts of Sumatra fall into the high category, while many eastern provinces remain in the medium to low groups. Kepulauan Riau Province scored the highest, while Papua Pegunungan scored the lowest. These results highlight the need for more equitable digital infrastructure development to support a more balanced and inclusive national digital economy transformation.